A calibration-free approach to detecting microRNA with DNA-modified gold coated magnetic nanoparticles as dispersible electrodes. Issue 46 (21st November 2022) - Hoque, Sharmin; Gonçales, Vinicius R.; Bakthavathsalam, Padmavathy; Tilley, Richard D.; Gooding, J. Justin
Abstract : Herein is shown an approach to using gold coated magnetic nanoparticles as dispersible electrodes for ultralow detection of circulating nucleic acids that requires no calibration to achieve quantitative information. Abstract : Gold coated magnetic nanoparticles (Au@MNPs), modified with DNA sequences give dispersible electrodes that can detect ultralow amounts of microRNAs and other nucleic acids but, as with most other sensors, they require calibration. Herein we show how to adapt a calibration free approach for electrochemical aptamer-based sensors on bulk electrodes to microRNA (miR-21) detection with methylene blue terminated DNA modified Au@MNPs. The electrochemical square wave voltammetry signal from the DNA-Au@MNPs when collected at a bulk electrode under magnetic control, decreases upon capture of miR-21. We show that the square wave voltammogram has concentration dependent and independent frequencies that can be used to give a calibration free signal.